2014
DOI: 10.1021/bc5005526
|View full text |Cite
|
Sign up to set email alerts
|

Cryptophane-Folate Biosensor for 129Xe NMR

Abstract: Folate-conjugated cryptophane was developed for targeting cryptophane to membrane-bound folate receptors that are overexpressed in many human cancers. The cryptophane biosensor was synthesized in 20 nonlinear steps, which included functionalization with folate recognition moiety, solubilizing peptide, and Cy3 fluorophore. Hyperpolarized 129Xe NMR studies confirmed xenon binding to the folate-conjugated cryptophane. Cellular internalization of biosensor was monitored by confocal laser scanning microscopy and qu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
49
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 38 publications
(50 citation statements)
references
References 72 publications
1
49
0
Order By: Relevance
“…To date, cryptophane-based sensors that use specific binding to the target have been implemented for sensing the enzyme MMP7, [142] nucleotides, [143] human carbonic anhydrase, [144] MHC class II, [145] zinc ions, [146] the glycoprotein CD14 [147] and the receptors for integrin, [148] transferrin, [149] EGF, [150] and folate. [151] An indirect binding approach was pursued through in situ click chemistry with metabolically labeled cell surface glycans. [152] Conformational changes of the sensor induced by changes in pH represent an approach for stimulus-induced binding.…”
Section: Xe Biosensor Applications In Cell Biologymentioning
confidence: 99%
“…To date, cryptophane-based sensors that use specific binding to the target have been implemented for sensing the enzyme MMP7, [142] nucleotides, [143] human carbonic anhydrase, [144] MHC class II, [145] zinc ions, [146] the glycoprotein CD14 [147] and the receptors for integrin, [148] transferrin, [149] EGF, [150] and folate. [151] An indirect binding approach was pursued through in situ click chemistry with metabolically labeled cell surface glycans. [152] Conformational changes of the sensor induced by changes in pH represent an approach for stimulus-induced binding.…”
Section: Xe Biosensor Applications In Cell Biologymentioning
confidence: 99%
“…13 Cryptophanes can be made water-soluble and provide a hydrophobic cavity with internal volume roughly double that of Xe ( D = 4.3 Å, V ≈ 40 Å 3 ). 13f–h, 14 Our laboratory 11, 15 and others 16 have designed cryptophane-xenon biosensors targeted to specific biomarkers indicated in cancer, including integrin 11b and folate receptors, 15b EGFR, 16h mIgM, 16i MMP-7, 17 and carbonic anhydrase. 15a Additionally, studies have demonstrated the use of xenon biosensors to target live cells.…”
mentioning
confidence: 99%
“…13f–h, 14 Our laboratory 11, 15 and others 16 have designed cryptophane-xenon biosensors targeted to specific biomarkers indicated in cancer, including integrin 11b and folate receptors, 15b EGFR, 16h mIgM, 16i MMP-7, 17 and carbonic anhydrase. 15a Additionally, studies have demonstrated the use of xenon biosensors to target live cells. 15c, 18 In these prior examples, Xe binding to cryptophane biosensors produced a specific hp 129 Xe NMR chemical shift, which shifted downfield when bound to protein analyte.…”
mentioning
confidence: 99%
See 2 more Smart Citations